Effect of branchings on blood flow in the system of human coronary arteries - Benchawan Wiwatanapataphee; Yong Hong Wu; Thanongchai Siriapisith; Buraskorn Nuntadilok (Mathematical Biosciences and Engineering)
In this work, we investigate the behavior of the pulsatile bloodflow in the system of human coronary arteries. Blood is modeled asan incompressible non-Newtonian fluid. The transient phenomena ofblood flow through the coronary system are simulated by solving thethree dimensional unsteady state Navier-Stokes equations andcontinuity equation. Distributions of velocity, pressure and wallshear stresses are determined in the system under pulsatileconditions on the boundaries. Effect of branching vessel on the flowproblem is investigated. The numerical results show that bloodpressure in the system with branching vessels of coronary arteriesis lower than the one in the system with no branch. The magnitude ofwall shear stresses rises at the bifurcation.